Enhancement of the Anti-biofilm Activity of Gold Nanoparticles- Itraconazole Conjugates in Resistant Candida glabrata - Lotfali, Ensieh; Fattahi, Mahsa; Ghasemi, Reza; Zakermashhadi, Farzan; Shafiei, Mohammad; Borzouie, Mojgan; Rabiei, Mohammad M. (Recent Advances in Anti-Infective Drug Discovery, 2021)
Introduction: Onychomycosis, also called tinea unguium, is a common fungal infection affecting the nails. After dermatophytes, Candida species are recognized as second-line pathogens responsible for this infection. The treatment of onychomycosis requires a long time and is associated with high rates of recurrence. Antifungal medicines conjugated with gold (Au-NP) nanoparticle are the possible platforms for the reduction of drug resistance. Methods: In the present study, we reported the in-vitro antifungal activity of itraconazole (ITZ) – Au conjugates, time-kill studies, and biofilm-producing ability of six ITZ-resistant C. glabrata. Results: 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium bromide (MTT) quantitative results revealed that four out of six resistant isolates studied able to form biofilms in vitro. ITZ-Au conjugates were more effective than ITZ or Au nanoparticle alone, and the time-kill tests pointed to the suitable effect of ITZ-Au conjugate. Conclusion: The present study concluded that ITZ-Au conjugates have an inhibitory effect on the biofilm of resistant C. glabrata isolates. Further studies are needed to compare the ex-vivo onychomycosis model.
Keywords: itraconazole